Miners strike, 1972 (page 1) (1972)
1972 1960-2000 "Miners strike, 1972 (page 1)" [T0444.jpg], 1972 Extract from the personal diary of Peter Clarney, a member of the National Union of Mineworkers, Yorkshire area during the miners strike 1972. He details his experiences of picketing at the West Midlands Gas Board coke depot at Saltley, Birmingham and meeting Arthur Scargill.